2022
DOI: 10.1158/1055-9965.epi-22-0904
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide and Glycidamide Hemoglobin Adduct Levels and Breast Cancer Risk in Japanese Women: A Nested Case–Control Study in the JPHC

Abstract: Background: Acrylamide (AA) is classified as “probably carcinogenic to humans (Class 2A)” by the International Agency for Research on Cancer. AA causes cancer owing to its mutagenic and genotoxic metabolite, glycidamide (GA), and its effects on sex hormones. Both AA and GA can interact with hemoglobin to hemoglobin adducts (HbAA and HbGA, respectively), which are considered appropriate biomarkers of internal exposure of AA. However, few epidemiological studies reported an association of HbAA and HbGA with brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…These findings are in general agreement with recent meta-analyses [94,95]. Meanwhile, we recently measured hemoglobin adducts of acrylamide and glycidamide (HbAA and HbGA) in erythrocytes collected from 125 breast cancer cases and 250 controls in a nested case-control study within the JPHC Study [96]. We found no statistically significant positive association for either HbAA or HbGA, but a positive association between HbGA/HbAA ratio and risk of breast cancer.…”
Section: Epidemiological Evidence From General Populations In Japansupporting
confidence: 91%
“…These findings are in general agreement with recent meta-analyses [94,95]. Meanwhile, we recently measured hemoglobin adducts of acrylamide and glycidamide (HbAA and HbGA) in erythrocytes collected from 125 breast cancer cases and 250 controls in a nested case-control study within the JPHC Study [96]. We found no statistically significant positive association for either HbAA or HbGA, but a positive association between HbGA/HbAA ratio and risk of breast cancer.…”
Section: Epidemiological Evidence From General Populations In Japansupporting
confidence: 91%
“…Regarding alcohol consumption, a study of Japanese men found that those who consumed ≥ 46 g and ≥ 69 g of alcohol per day had a respective 40% and 60% higher risk of developing cancer than those who consumed < 23 g of alcohol per day [ 5 ]. Diet, physical activity, and body weight control are suggested as important factors based on epidemiological evidence [ 6 - 9 ]. In Japan, the population-attributable fraction of cancer due to preventable factors is estimated to be about 55% for male and about 30% for female.…”
Section: Introductionmentioning
confidence: 99%